Analisis Kuantitatif Perkataan-perkataan dalam Surah Al-Muawwidhat - Raja Yusof, Raja Jamilah; Mohd Yusoff, Zulkifli (Jurnal Usuluddin, 2004)
There are three surahs which are categorized as al-Muawwidhat. They are al-Ikhlas, al-Falaq and al-Nas. Rasullullah saw encourages the recitation of these surahs each time after prayer to protect the reciters from the danger of the evil doings of human. This article also puts forward the virtues of surah al-Muawwidhat, analyses the total number of words and comparison of words in the surahs. The results of the analysis will he put forward in the form of graphs and tables.